A decade of coral reef monitoring in Guadeloupe (Lesser Antilles) - Hanna-May Malahel; Christelle Batailler; Pascal Claquin; Charlotte R. Dromard (Frontiers in Marine Science, 2026)
Introduction Coral reefs of Guadeloupe have undergone substantial ecological degradation over the past decade, driven by cumulative disturbances including mass bleaching events, the emergence of Stony Coral Tissue Loss Disease (SCTLD), repeated Diadema antillarum die-offs and recurrent cyclones. Methods A 10-year dataset (2014-2024), from the European Water Framework Directive, combining physicochemical measurements, benthic composition and herbivorous fish census, was used to assess the changes in the overall health status of 14 coral reefs located around Guadeloupe (Lesser Antilles). Results Results show that benthic communities had already shifted toward algal dominance prior to the monitoring period, but that coral decline has accelerated markedly after 2020 in response to major environmental crises. Multivariate analyses identify turbidity, nutrient enrichment and chlorophyll concentrations as the primary drivers of benthic differentiation, with eutrophicated sites exhibiting high macroalgal cover and reduced coral recruitment. In contrast, reefs exposed to clearer oceanic waters maintained higher proportions of calcifying organisms and diversified herbivore assemblages. Spatial variability therefore reflects the interplay between regional disturbances and site-specific hydrological conditions. Conclusion These findings underscore the increasing vulnerability of Guadeloupean reefs and highlight the need to reduce land-based nutrient inputs, improve wastewater management, and preserve herbivore communities to sustain the remaining coral communities and their ecological functions.